(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This research deals with a non-invasive system that can be used to harvest waste mechanical energy and utilise this energy to suppress tremors. Hand tremors can emanate from medical conditions such as Parkinson disease and Arthritis. These tremors can be distinguished from other vibrations due to the associated frequency spectra. Mechanical signals are picked up by piezoelectric sensors before the generated voltage is filtered, converted and stored, or used directly to suppress the tremor. Two system level methods used for the suppression of tremor are discussed. As the device is proposed for glove structures, material flexibility is of key significance thus not hindering the bearer’s motor functions. Conventional piezoelectric ceramic materials are recognised for their high piezoelectric coefficients in comparison to flexible piezoelectric polymer films. However, ceramic materials are rigid, heavy and offer limited opportunities for forming and shaping. Ceramic based piezoelectric materials in fine fibre form across a range of diameters (10-250&#956m) were used in this research. When integrated into composite structures the resulting materials retained all the qualities of bulk piezoelectric ceramics (electrical, mechanical, chemical) and mitigated the disadvantages of weight and brittleness. Various piezoelectric fibre composites and piezoelectric polymer film structures were compared, and the potential for their exploitation in glove based power harvesting and tremor suppression structures assessed.